The Effectiveness of the Penal System in Addressing Domestic Violence Offenders in Indonesia - Mahendra, Diko Alando; Issalillah, Fayola; Safira, Mirza Elmy (Metromedia, 2023)
This research examines the effectiveness of the punishment system against perpetrators of domestic violence (KDRT) in Indonesia with a normative juridical approach. The main focus is to analyze the applicable laws and regulations, the implementation of criminal penalties, and the role of law enforcement institutions in providing protection for victims. Domestic violence, which includes physical, psychological, sexual and economic aspects, is a serious crime that has a wide-ranging impact on families and society. Although Law No. 23/2004 on the Elimination of Domestic Violence has been implemented, many challenges remain, including in the implementation of the criminal justice system. This study found that law enforcement is often constrained by a lack of understanding of victim protection, less than optimal criminal sanctions, and weak coordination between related institutions. By analyzing legal literature and case studies, this research provides recommendations to strengthen the existing legal system, including through strengthening victim protection mechanisms, educating the public, and reforming criminal policy. This research aims to provide an academic contribution in improving the criminal law system related to domestic violence, as well as increasing its effectiveness in creating justice and protection for all parties involved.